General Takaful claims: An experience of Takaful operator in Malaysia / Amirul Afif Muhamat, Mohamad Nizam Jaafar and Sharifah Faigah Syed Alwi. - Muhamat, Amirul Afif; Jaafar, Mohamad Nizam; Syed Alwi, Sharifah Faigah (Universiti Teknologi Mara Selangor, 2017)
Takaful is interchangeably referred as Islamic insurance. In Malaysia, the takaful sector is part of the main components for Islamic finance industry. The business can be divided into two: general and family takaful. To ease understanding on this niche sector; general takaful is comparable to general insurance while family takaful is akin to life insurance with special reference needs to be given on the requirement of the business to adhere to the Islamic precepts. The main business in general takaful is motor takaful and this line of business is faced with high takaful claims. This study appraised the factors which affect the general takaful claims based on the experience of one takaful operator in Malaysia (the name of takaful operator is not disclosed due to confidentiality). The factors are: number of claims; fraud; and coverage for protection. The limitation of this study is that the observation period is only 10 years which limits rigorous analysis to be done. Nevertheless, previous studies in this area depict the same limitation – constraint in gathering data that has long observation period. On the bright side, the data in this study is still capable to produce meaningful results to be referred with regards to this issue – general takaful claims.